137k views
3 votes
Needing some help please!!

Needing some help please!!-example-1
User Grodriguez
by
5.8k points

1 Answer

0 votes

Answer:

a. 2

b. 3

c. 3x^2+9x+15

d. 257

Explanation:


f(x)=x^(2)+1 \\g(x)=3x+4 \\

When a function is written like that the value in the parenthesis is what you use to replace the x inside the expression.

a. f(-1) means the value of function "f" when x = -1


f(-1)=(-1)^(2)+1=1+1=2

b. "f" when x = -2 + "g" when x = -2


f(-2)+g(-2)=(-2)^(2)+1+3(-2)+4=3

c. multiply for 3 each function


3f(x)+3g(x)=3(x^(2)+1)+3(3x+4)=3x^(2)+9x+15

d. "g" when x = 4 then "f" when x = g(4)


g(4)=3(4)+4= 16\\f(g(4))=f(16)=16^(2)+1 = 257

User Clerenz
by
5.8k points